Placental thickness measurement at second and third trimester and its association with fetomaternal outcome - Magoo, Prerna; Agarwal, Shivani; Yadav, Vaishali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Placenta is responsible for adequate foetal growth and development by performing nutritional, endocrine, excretory, respiratory and countless other important functions. Studying the architecture and morphology of placenta on USG antenatally can tip-off about health of the foetus in utero. Methods: A prospective observational study was conducted at Kasturba Hospital, Delhi, from August 2023 to October 2024. The minimum required sample size was estimated to be 36 Considering a 95% confidence level, 90% power and an absolute error of 5% and a correlation coefficient of 0.51 between placental thickness and neonatal birth weight as reported by Gauri Raghunath Shinde et al.1 A total of 42 pregnant women were enrolled in the study in their first or second trimesters. Ultrasonography for placental thickness (PT) was performed at 25 and 35 weeks period of gestation (POG). Patients were followed up till delivery and various foetal and maternal outcomes such as birth weight, Pregnancy Induced hypertension (PIH), intrauterine growth restriction (IUGR), Gestational Diabetes Mellitus (GDM), Intrahepatic Cholestasis of pregnancy (IHCP) among many more were recorded. Statistical analysis was performed using SPSS-25 and a p-value <0.05 was considered significant. Results: Mean PT at 25 weeks POG was found to be 26.29+4.47 mm and at 35 weeks POG was found to be 33.23 ±5.74 mm. Posterior wall placentae were found to be thicker as compared to anterior wall implanted placentae (at 25 weeks POG mean PT for anterior vs posterior placentae were 24.72 vs 27.57; at 35 weeks POG mean PT for anterior vs posterior placentae were 30.22 vs 35.44). Birth weight was found to increase with increase in PT (at 25 weeks POG Pearl’s correlation coefficient R= 0.36, p=0.02; at 35 weeks POG Pearl’s correlation coefficient R= 0.479, p=0.002). Pregnant Women (PW) with normal PT (>-2SD;<2SD) and thick PT (>2SD) at 25 weeks POG had mean birth weights 2.85kg and 3.13kg respectively. PW with thin (<-2SD), normal thickness (>-2SD; <2SD) and thick placentae (>2SD) at 35 weeks POG had mean birth weights 2.51kg, 2.85kg and 3.18kg respectively. Conclusions: Measurement of PT antenatally on sonography can indicate about health of foetus in utero and its outcomes in the postnatal life.